PENGARUH PEMBERIAN PACLOBUTRAZOL TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT (Lycopersicum esculentum Mill.) DENGAN PEMANGKASAN SATU CABANG UTAMA - Edy Syaputra; Nurbaiti Nurbaiti; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aims to determine the effect of application some concentration of paclobutrazol and to obtain the best concentration on the growth and yield of tomato with one main branch pruned. The research was conducted experimentally by using Completely Randomized Design with treatment of application some concentration of paclobutrazol (K) consist of four levels that is: K0 : without application of paclobutrazol (control), K1 : 300 ppm, K2 : 600 ppm and K3 : 900 ppm. Data were examined using analysis of variance and mean separations with Duncan’s New Multiple Range Test at the 5% level.The results showed that the application of paclobutrazol on tomato plants by pruning the main branches can inhibit plant height and accelerate age appear first interest and does not make a difference by being deprived of paclobutrazol on the parameters of stem diameter, number of flowers per plant, the age of the first harvest, the amount of fruit per plant, weight of fruits per plant and fruit diameter. Keywords: paclobutrazol concentrate, growth and yield, tomato plant.